What Drives Digital Marketing Adoption in Resource-Constrained MSMEs? Evidence Using a TOE-Led Integrative Framework - Xavier, Bibin; Vanitha, A. (International Review of Management and Marketing, 2025)
This study examines how technology, organization, and environmental factors influence MSME intention and digital-marketing adoption. Based on TOE, TAM, and DOI models of adoption and estimated using CB-SEM on a cross-sectional survey using validated scales, the results find intention as the dominant pathway to adoption. Intention rises with perceived ease of use, compatibility/capabilities, relative advantage, trust, knowledge, and customer/competitive pressure, and falls with perceived financial cost; strategic—but not tactical—digital-marketing orientation contributes incremental explanation. Tests of mediation find that most antecedents impact adoption via intention. The results position ease-of-use and skill-training centre- stage, trust-building and capability-building, and selective cost relief as means of converting intention into use and offer district-level guidance for policymakers and incubators, and encouragement for future longitudinal follow-up.